Relasi Antara Demokrasi, Partai Politik, Dan Pemilu - Ubaidillah, Ibnu (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2021)
Democracy, political parties, and elections, are terms that are no longer foreign to our ears. This paper wants to discuss the relationship between democracy, political parties, and elections. By using the analytical descriptive method, it is concluded that the relationship between democracy, political parties and elections in general is basically a logical consequence of the implementation of modern democratic practices. Modern democracy based on representative democracy requires the establishment of an instrument of democracy as the main support for the implementation of the practice of representative democracy. Even in a more extreme perspective, there are those who say that without the two instruments of democracy (political parties and elections), the practice of representative democracy is impossible to run optimally.